Diversity confirms its vote: transsexuals candidacies, folkcommunication and political representation (Revista Internacional de Folkcomunicação, 2021)
The purpose of this article is to reflect on the spaces occupied by transsexual candidates in the last municipal elections of 2020, in Brazil, correlating folk communication, political representation and minorities. Despite the electoral success of a still small portion of this segment across the country, with greater prominence in large cities, transsexuals reinforce their gender policies and open up new fields of political disputes, as never before seen in Brazilian society. In this perspective, the work points out how media visibility enhances affirmative communication policies for transsexual identity, which have enabled plural readings of society, opening new spaces and democratizing political representation. Folkcommunication; Political Representation; Minorities; Transsexuals.